2022
DOI: 10.1093/hropen/hoab046
|View full text |Cite
|
Sign up to set email alerts
|

The risk of miscarriage following surgical treatment of heterotopic extrauterine pregnancies

Abstract: Study Question What is the risk of loss of a live normally sited (eutopic) pregnancy following surgical treatment of the concomitant extrauterine ectopic pregnancy? Summary Answer In women diagnosed with heterotopic pregnancies, minimally invasive surgery to treat the extrauterine ectopic pregnancy does not increase the risk of miscarriage of the concomitant live eutopic pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The standard management for HP remains unknown due to the rarity of this disease. Surgical treatment is the most frequently choice for HP ( 8 11 ). With the development of equipment and techonology, clinicians have put more and more attention to laparoscopy, rather than open surgery ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard management for HP remains unknown due to the rarity of this disease. Surgical treatment is the most frequently choice for HP ( 8 11 ). With the development of equipment and techonology, clinicians have put more and more attention to laparoscopy, rather than open surgery ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no clinical guidelines or expert consensus to provide the standard management recommendation for HP due to its rarity. Surgery has been the most common treatment of choice in patients with HP, especially for those with unstable clinical sign or EP ruptures (8)(9)(10)(11). Open approach (OA) is the traditional surgical method for HP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscarriage rates reached up to 26% in women who had surgical treatment ( 24 ). Others demonstrated that surgical treatment of heterotopic extrauterine pregnancies did not increase the risk of miscarriage of the concomitant live eutopic pregnancy ( 25 ). In our report, among 14 patients who received surgery with pregnancy outcomes, 10 patients resulted in the delivery of full-term neonates, while 2 patients had spontaneous abortion or fetal arrest.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] However, with the increased application of assisted reproductive techniques (ART) such as in vitro fertilization and artificial insemination (AI), the incidence of HP in a woman with ART treatment has raised to approximately 1%. [3][4][5] It is essential to diagnose and treat HP as soon as possible to avoid severe complications, such as hypovolemic shock, emergency blood transfusions, maternal mortality, and fetal loss. The early and accurate diagnosis of HP remains challenging due to the presence of IUP.…”
Section: Introductionmentioning
confidence: 99%